A Comprehensive Dataset for Bibliometric Analysis of Sustainable Entrepreneurship with Augmented Bibliometric Approach - Dian Perwitasari; An Nurrahmawati; Heri Susanto (Journal of Theoretical and Applied Management (Jurnal Manajemen Teori dan Terapan), 2023)
Objective: The issue of Sustainable Entrepreneurship (SE) has attracted significant attention in recent years, aligning with the concerted global efforts to carry out the SDGs for 2030. Hence, this study aimed to analyze state of the art in SE research to navigate the result of international publication trends regarding SE for 20 years. Design/Methods/Approach: This study uses bibliometric analysis to explore the evolution of streams of 338 papers from the Scopus database spanning from 2003 to 2022, including identifying the evolution of publications, contributions of authors, countries, and core journals to a field. In addition, we use the Augmented Bibliometric Approach by mapping and visualizing trend analysis of bibliographic coupling, co-citation, and co-author relationships of datasets, using VOSviewer 1.6.19. Findings: The result showed a consistent upward trajectory in publications from 2015 onwards. Furthermore, our study showed influential authors, papers, countries, and journals within this domain. Originality/Value: This study contributes to elucidating the evolution of SE, serving as a valuable resource for future studies, aiding in the formulation of theoretical frameworks, and facilitating advancements in this area. Practical/Policy implication: Given the results, managers should apply various techniques to minimize the negative impact of their business continuity, a strategic approach towards the triple bottom line. Practitioners and policymakers should be able to interpret innovations in sustainability assessment systems further to enable them to formulate policies, strategies, and guidelines to promote the sustainable development agenda (SDGs).